Sistem Pembelajaran Kosakata Bahasa Inggris Berbasis Web Menggunakan Metode Rapid Application (RAD) - Aprinia Handayani; Samsoni (LPPM Politeknik Aceh Selatan, 2024)
English lexicon dominance is one of the imperative viewpoints in dialect learning at the Kindergarten (TK) level. Be that as it may, ordinary strategies utilized in lexicon learning are frequently less curiously and less successful in spurring understudies to memorize. The foundation of this think about is the require for a more interactive learning framework that's in understanding with innovative advancements to back the educating and learning handle at TK Al Amanah. The issue confronted is how to plan a lexicon learning framework that can increment students' intrigued and understanding successfully. As a arrangement, this consider proposes the improvement of a web-based English lexicon learning framework utilizing the Fast Application Advancement (RAD) strategy. The RAD strategy was chosen since it is able to create quick models and include clients in each organize of improvement, so that the coming about system can be more in agreement with the requirements of clients, in this case understudies and instructors at TK Al Amanah. The framework developed includes highlights such as intelligently works out, advanced flashcards, and tests planned to create it simpler for understudies to memorize and get it lexicon. The investigate strategy includes needs examination, framework plan, model advancement, testing, and assessment. The trial comes about appear that this framework isn't only able to extend understudy inspiration and interest, but too gives comfort for instructors in conveying learning materials. Hence, this web-based learning framework offers an innovative solution that can bolster the method of educating English lexicon at the kindergarten level